Digital Banking, Corporate Governance, Ownership Structure, and Intellectual Capital Performance: Evidence from Indonesia - Ratna Dewi Tjendani; Ari Kuncara Widagdo; Muthmainah Muthmainah (University of Merdeka Malang, 2018)
The base of the company’s growth has changed, from tangible assets to intangible assets. Many companies recognize the importance of IC as performance drivers. This research aimed to examine the effect of the implementation of digital banking, corporate governance, family ownership, foreign ownership, and government ownership on Intellectual Capital (IC) performance; and examined the effect of interactions between corporate governance and ownership structure on IC performance in banking companies listed on the Indonesia Stock Exchange (IDX) during 2012-2016. This research used a regression method with panel data. The total observations were 130 cases. In this research, IC performance used Value Added Intellectual Coefficient (VAIC). We proved that the implementation of digital banking did no significant implications for IC performance in the same year because it was still in the process of developing. Family ownership, foreign ownership, government ownership, and the interaction between corporate governance and ownership structure did not affect IC performance. On the contrary, this research proved that corporate governance had significant implications for improving IC performance. JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v22i4.2481